Liver Resection and role of Extended Histology (LiREcH study) in patients with multifocal colorectal cancer liver metastases. Issue 10 (October 2021) - Bari, Hassaan; Thiyagarajan, Umasankar M.; Brown, Rachel; Roberts, Keith J.; Chatzizacharias, Nikolaos; Marudanayagam, Ravi; Muiesan, Paolo; Isaac, John; Mirza, Darius F.; Sutcliffe, Robert P.; Dasari, Bobby V.M.
Abstract: Background: The aim of this study is to assess the correlation between the margin status on the specimen side (Rs) and that from the patient side (base of resection) (Rp) and the influence of positive margins (R1s and R1p) on cancer related outcomes in patients with colorectal liver metastases (CRLM). Methods: In this prospective study, patients undergoing non-anatomical resection (NAR) of multifocal CRLM, with suspected close resection margins were included. The primary outcome evaluated was the correlation of Rs and Rp. Results: Twenty-three patients had 89 NARs, and CUSA samples from the base of 36 specimens were analysed. Among 36 specimens where extended histology (EH) was performed, margin status on the specimen side (Rs) was positive in 69.4% (25/36), whereas on the patient side, the margin (Rp) was positive in only 8.3% (3/36) of specimens. On univariate analysis, there was no significant difference in the site-specific recurrence at previous resection with regards to Rs positivity (P = 0.56) and Rp positivity (P = 0.48). Conclusion: There is a poor correlation between Rs and Rp and the local recurrence rates in the liver. These results might further support that tumour biology is more relevant than the margin status in patients with multifocal CRLM.